Effects of ultrasonic treatment on the physicochemical, structural, and functional properties of soluble dietary fiber from coffee peels - Xinxin Yu; Ke Zhu; Faguang Hu; Rongsuo Hu; Wenjiang Dong (Ultrasonics Sonochemistry)
Coffee peel (CP) is an important by-product of coffee processing which is rich in bioactive components. In the present work, we extracted coffee peel soluble dietary fiber (CSDF) via ultrasound-assisted alcohol precipitation to reduce resource waste as well as environmental pollution and evaluate its structure, monosaccharide composition, and functional and physicochemical characters. Based on our findings, ultrasonic treatment decreased particle size of CSDF from 131.49 ± 7.67 μm to 75.84 ± 1.20 μm, and markedly improved the homogeneity. The ultrasonic power of 200–300 W resulted in increased thermal stability due to a higher crystallinity of the CSDF. Increasing the ultrasonic power (0–500 W) reduced rhamnose level from 8.25 % to 7.61 % (p < 0.05) and the SDF treated with 100 W of ultrasonic power had the highest fructose content (21.37 %). The ultrasonic treatment improved the water-solubility, oil-holding capacities and water-holding capacities of CSDF, with highest water-holding capacity being obtained at 300 W (8.92 ± 1.57 g/g). Additionally, the glucose and nitrite ion adsorption capacities significantly improved after ultrasonic modification. These findings may expand the application of CSDF in the food industry.